Assemblages and Subassemblages of Giardia duodenalis in Rural Western, Kenya: Association with Sources, Signs, and Symptoms - Erick Barasa; Briston Indieka; Nathan Shaviya; Ezra Osoro; Geofrey Maloba; Denis Mukhongo; Valentine Budambula; Tom Were (Journal of Parasitology Research)
Background. Giardia duodenalis causes sporadic or epidemic infections in humans. The parasite comprises assemblages A-H with A and B subdivided further into AI-IV and BI-IV subassemblages. Attempts aimed at linking these genotypes with sources and gastrointestinal manifestations of the infection are largely unexplored in rural communities. Methods. In this cross-sectional study, G. duodenalis infection was genotyped and associated with sources, and gastrointestinal signs and symptoms of the disease among residents of Busia County, a rural setting in western Kenya. Demographic and clinical information were captured using standardized forms. Stool specimens were obtained from the patients and used for genotyping at glutamate dehydrogenase and triose-phosphate isomerase loci using the polymerase chain reaction and restriction fragment length polymorphism. Results. Assemblage B (63.6%) was the most prevalent G. duodenalis infection, while A (20.5%) and mixed A/B (15.9%) were also detected. Among the subassemblages, AI (5.7%), AII (8.0%), AIII (3.4), BIII (30.7%), and BIV (17.0%) were diagnosed including the mixed AII/BIII (15.9%), BIII/BIV (15.9%), AI/AIII (2.3%), and AI/AII (1.1%) infections. Binary logistic regression indicated associations for assemblage A with stomach upset, history of nitroimidazole treatment, and residing in a homestead with cattle and B with age<18 years, history of eating outdoors, vomiting, steatorrhea, and residing in a homestead with cattle, goats, and poultry (p<0.05 for all). Among the subassemblages, associations were found for AI with residing in a homestead having cattle and history of nitroimidazole treatment, BIII with residing in a homestead having cattle and poultry, and BIV with steatorrhea (p<0.05 for all). Altogether, this study illustrates that G. duodenalis assemblage B and subassemblage BIII are the most predominant and are linked to age<18 years, gastrointestinal manifestations, and living in a homestead with domestic ruminants and poultry. Conclusion. Targeted mass prophylactic treatment of domestic animals and utilization of gastrointestinal presentations, age<18 years, and a history of nitroimidazole use are useful in the diagnosis and prevention of giardiasis among residents of rural communities.